Immediate placement and loading of implants in anterior maxilla using an altered screw-retained implant fixed prosthesis. - Baig, M.R.; Rajan, G. (2010)
This article describes the immediate placement and loading of implants in the aesthetic zone using an implant-retained, fixed prosthesis with a modified design. One section of the implant prosthesis has cemented crowns and the other section is the conventional screw-retained. This combined approach significantly offsets the unsuitable implant position, alignment or angulation, while ensuring the easy retrievability, repair and maintenance of the prosthesis at the same time.